La gestión administrativa y su incidencia en la atención al cliente de la Cooperativa de Ahorro y Crédito integración desarrollo y futuro INDESFUT LTDA - Juan Andres, Cambi Cevallos (2021)
Abstract This work was carried out to establish whether the administrative management of the “Cooperativa de Ahorro y Crédito Integración, Desarrollo y Futuro INDESFUT LTDA” affects customer service. For this, it is taken into account that savings and credit cooperatives are private institutions whose purpose is to help their members to improve their lifestyle by having access to financial services such as loans, creation of savings accounts, service payment points essential, among others. In Ecuador, their presence has favored small agricultural producers, businesses, and families. Every financial or non-financial institution must maintain control related to the quality of the service provided to customers. So it is necessary to investigate where the organization's internal and external deficiencies could permit preventive and corrective measures to be taken. Thereby can direct the resources, activities, and times to achieve the adequate administration's efficiency and effectiveness to achieve the mission. Set out in the savings and credit cooperative, with which an inquiry was made where the existence of philosophy, of the established organization chart, is appreciated. An interview was structured for the organization's workers and surveys to know the members' perspectives. With the data obtained from the interviews carried out, it was possible to conclude the cooperative failures, which are focused on the lack of a training plan that promotes the collaborators' personal and professional development. Additionally, there is no budget allocated for the purpose, and with the survey data, a problem concerning safety is evidenced, so it is recommended to improve it, with which customer service can significantly improve. Keywords: Administrative management, Training plan, Resources, Customer service. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783